Advances in pharmacotherapy for the treatment of allergic rhinitis; MP29-02 (a novel formulation of azelastine hydrochloride and fluticasone propionate in an advanced delivery system) fills the gaps. (April 2015) - Bousquet, Jean; Bachert, Claus; Bernstein, Jonathan; Canonica, G Walter; Carr, Warner; Dahl, Ronald; Demoly, Pascal; Devillier, Philippe; Hellings, Peter; Fokkens, Wytske; Klimek, Ludger; Lieberman, Phil; et al.
Abstract : Introduction: Effective pharmacologic treatment exists for most patients suffering from allergic rhinitis (AR). However, both in clinical trials and in real-life studies, many patients are dissatisfied with treatment. Physicians often use multiple therapies, in an attempt to improve symptom control, often with limited evidence of success. Novel treatment options are needed and must consider unmet medical needs. Areas covered: This article reviews the clinical data for a new AR treatment.MP29-02 (Dymista®, Meda, Solna, Sweden) contains azelastine hydrochloride (AZE) and fluticasone propionate (FP), in a novel formulation and delivered in an improved device as a single nasal spray. It has shown superior efficacy in AR patients than either commercially available AZE or FP monotherapy for both nasal and ocular symptom relief, regardless of disease severity. MP29-02 also provided more effective and rapid symptom relief than either AZE or FP monotherapy delivered in the MP29-02 formulation and device. However, the effect was less than that observed versus commercial comparators, suggesting the impact of formulation and device on clinical efficacy. Expert opinion: MP29-02 simplifies AR management, surpassing the efficacy of gold standard treatment, intranasal corticosteroids (INS), for the first time. It is indicated for the treatment of moderate-to-severe seasonal allergic rhinitis and perennial allergic rhinitis when monotherapy with either intranasal antihistamine or INS is NOT considered sufficient. Most patients present with moderate/severe disease, with evidence of current or previous treatment insufficiency. MP29-02 should be the treatment of choice for these patients.